Christians in Caesar's household: the emperors' slaves in the makings of Christianity - Flexsenhar, Michael III (Inventing Christianity, 2021)
Frontmatter -- CONTENTS -- List of Illustrations -- Acknowledgments -- List of Abbreviations -- Introduction -- 1 Paul, the Philippians, and Caesar’s Household (Phil 4:22) -- 2 Paul, Peter, and Nero’s Slaves: Martyrdoms and Apostolic Acts -- 3 Rome’s Imperial Household in Christian Polemic and Apologetic -- 4 Christian Piety and a Martyred Slave of Caesar -- 5 Material Evidence for a Christian Imperial Freedman -- 6 Christians and Imperial Personnel in Rome’s Catacombs -- Conclusion: The Memory of Imperial Slavery in Early Christianity -- Appendixes -- Notes -- Bibliography -- Index